Psychological and Organizational Factors Influencing Fraud Reporting in Organizations: A Systematic Literature Review - Aryanti, Rr. Feni; Hasanati, Nida (International Journal Labs, 2024)
Whistleblowing is a crucial mechanism for maintaining organizational integrity by exposing unethical or illegal activities such as fraud, data manipulation, and policy violations. This study systematically reviews the psychological and organizational factors influencing whistleblowing behavior. Key psychological factors include moral responsibility, risk perception, self-control, and Machiavellianism, which can either encourage or deter individuals from reporting unethical conduct. Organizational factors such as culture, institutional support, and whistleblower protection policies significantly shape reporting intentions. Demographic and social factors, including age and proximity to fraudsters, also play a critical role. The review highlights that gaps exist in understanding how religious values, organizational structures, and protection mechanisms impact whistleblowing behavior. Addressing these gaps, this review provides recommendations for future research, emphasizing the need for robust organizational policies and support systems to foster transparency and accountability. By answering key research questions and identifying overlooked aspects, this review contributes to the theoretical and practical understanding of whistleblowing, offering insights for organizations across various sectors to encourage effective fraud reporting.